Relación entre las propiedades químicas del suelo, la composición química y las propiedades físicas de madera de Acacia macracantha Humb. & Bonpl. ex Willd, en la ciudad de Loja - Chimbo Granda, María Belén (2024)
Trees are essential in the urban environment since they provide multiple environmental, aesthetic and social benefits which are used by citizens. In the city of Loja, 91 forest species have been identified, including Acacia macracantha Humb. & Bonpl. ex Willd (faique), a native of the Fabaceae family. This multipurpose species is used in reforestation processes, restoration of degraded areas and in green areas, in addition to offering important ecosystem services. In the present research, the physical properties and chemical composition of Acacia macracantha wood were determined, as well as its relationship with the soil of urban trees in Loja. The plant material was obtained from the branches of five trees, from which seven cylindrical specimens were extracted for each individual. Under laboratory conditions, moisture content, basic density and volumetric shrinkage were determined, and the chemical composition of the wood (extractives, holocellulose, lignin and ash) was determined using the Technical Association of the Pulp and Paper Industry (TAPPI) standard. Soil analysis included pH, nitrogen (N), phosphorus (P), potassium (K) and organic matter (OM), this analysis was performed by zig-zag sampling near the selected trees. The data were analyzed using descriptive and quantitative statistics. To establish the relationship between variables, principal component analysis (PCA) was applied. Acacia macracantha wood presented a moisture content of 39.21 %, a basic density of 0.66 g/cm3 and volumetric shrinkage of 21.22 %. Regarding its chemical composition, holocellulose was the most abundant component with 57.26 %, followed by lignin with 37.31 % and in smaller quantities were found extractives with 3.39 % and ash with 1.44 %. The soil where this species grows is slightly alkaline (pH= 7.63) and presents high levels of N, P, K, with a medium level of OM. A positive relationship was observed between volumetric shrinkage and pH and potassium, and inversely with phosphorus and nitrogen. There was also a relationship between ash and holocellulose with potassium and pH. In conclusion, the chemical properties of the soil influence the physical properties and the amount of chemical components of Acacia macracantha wood